Design, synthesis and biological characterization of selective LIMK inhibitors. Issue 18 (15th September 2015) - Boland, Sandro; Bourin, Arnaud; Alen, Jo; Geraets, Jacques; Schroeders, Pieter; Castermans, Karolien; Kindt, Nele; Boumans, Nicki; Panitti, Laura; Vanormelingen, Jessica; Fransen, Silke; Van de Velde, Sarah; et al.
Graphical abstract: Abstract: Inhibitors of LIM kinases are considered of interest for several indications, including elevated intraocular pressure (IOP), cancer, or infection by HIV-1. LX-7101 (Lexicon Pharmaceuticals) was advanced to Phase-I clinical trials as an IOP-lowering agent for treatment of glaucoma. We here discuss the design, synthesis and evaluation of LIMK inhibitors based on a pyrrolopyrimidine scaffold, which represent close analogs of LX-7101. Exploration of structure–activity relationships revealed that many of such compounds, including LX-7101, cause potent inhibition of LIMK1 and LIMK2, and also ROCK2 and PKA. Molecular variations around the various structural elements of LX-7101 were attempted. Substitution on position 6 of the pyrrolopyrimidine scaffold led to the identification of LX-7101 analogs displaying good selectivity versus ROCK, PKA and Akt.